logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

Prove that \[cos^{-1} \frac {4}{5} +cos^{-1} \frac{12}{13}=cos^{-1} \frac{33}{65}\]

Can you answer this question?
 
 

1 Answer

0 votes
Toolbox:
  • \( cos^{-1}x+cos^{-1}y=cos^{-1} (xy- \sqrt{1-x^2} \sqrt{1-y^2} )\)
Given $cos^{-1} \large\frac {4}{5} +cos^{-1} \large\frac{12}{13}$
We know that \( cos^{-1}x+cos^{-1}y=cos^{-1} (xy- \sqrt{1-x^2} \sqrt{1-y^2} )\)
 
By taking \(x=\large\frac{4}{5}\:and\:y=\large\frac{12}{13}\)in the above formula, we get
\(cos^{-1}\large\frac{4}{5}+cos^{-1}\large\frac{12}{13}=\) \( cos^{-1} \bigg[ \large\frac{4}{5}.\large\frac{12}{13}-\sqrt{1-\large\frac{16}{25}} \sqrt{1-\large\frac{144}{169}} \bigg]\)
\(= cos^{-1} \bigg[ \large\frac{48}{65}-\large\frac{3}{5}.\large\frac{5}{13} \bigg]=\:cos^{-1}\big(\large\frac{48}{65}-\large\frac{15}{65}\big)\)
\( =cos^{-1} \large\frac{33}{65}\) = R.H.S
 

 

answered Feb 23, 2013 by thanvigandhi_1
edited Mar 15, 2013 by thanvigandhi_1
 
Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...